Poloxamer 407 and Hyaluronic Acid Thermosensitive Hydrogel-Encapsulated Ginsenoside Rg3 to Promote Skin Wound Healing - Peng, Xiaojuan; Ding, Chuanbo; Zhao, Yingchun; Hao, Mingqian; Liu, Wencong; Yang, Min; Xiao, Fengyan; Zheng, Yinan (Frontiers in Bioengineering and Biotechnology, 2022)
Ginsenoside Rg3 has shown beneficial effects in various skin diseases. The current interest in designing and developing hydrogels for biomedical applications continues to grow, inspiring the further development of drug-loaded hydrogels for tissue repair and localized drug delivery. The aim of the present study was to develop an effective and safe hydrogel (Rg3-Gel), using ginsenoside Rg3, and we evaluated the wound-healing potential and therapeutic mechanism of Rg3-Gel. The results indicated that the optimized Rg3-Gel underwent discontinuous phase transition at low and high temperatures. Rg3-Gel also exhibited good network structures, swelling water retention capacity, sustainable release performance, and excellent biocompatibility. Subsequently, the good antibacterial and antioxidant properties of Rg3-Gel were confirmed by in vitro tests. In full-thickness skin defect wounded models, Rg3-Gel significantly accelerated the wound contraction, promoted epithelial and tissue regeneration, and promoted collagen deposition and angiogenesis. In addition, Rg3-Gel increased the expression of autophagy proteins by inhibiting the MAPK and NF-KB pathways in vivo. It simultaneously regulated host immunity by increasing the abundance of beneficial bacteria and the diversity of the wound surface flora. From these preliminary evaluations, it is possible to conclude that Rg3-Gel has excellent application potential in wound-healing drug delivery systems.